Analisis Kesesuaian Penerapan Strategi Pembelajaran Fiqih di MIN 1 HSU dengan Perkembangan Kognitif Peserta Didik - nabilastiq6b; Hikmatu Ruwaida; Juhairiah; Munirah (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
This research is based on the importance of implementing learning strategies that are appropriate to the state of cognitive development of students. The purpose of this study was to describe the suitability of the application of the fourth grade Fiqh learning strategy at Madrasah Ibtidaiyah Negeri 1 Hulu Sungai Utara (MIN 1 HSU) for the 2021/2022 academic year for the development of students. This research uses descriptive method which is a type of qualitative research. Data collection techniques were carried out by direct observation, interviews and documentation of research-related matters. The data obtained in this study were analyzed using the Miles and Huberman model, namely by reducing, displaying and verifying the data. The results showed that the implementation of class IV Fiqh learning strategies at MIN 1 HSU was in accordance with the stages of cognitive development of students. The type of strategy applied is a direct learning strategy which is carried out with lectures, questions and answers, and practice.